YOUTHS PROTEST IN NIGERIA: THE ENDSARS IN PERSPECTIVE - Felix Ikalewumi (International Studies Journal)
This paper explored youths’ protests in Nigeria. Unarguably, youths are assets imbued for national development arising from their strengths, potentials and initiatives when galvanize, empower and streamline into the national wealth. However, where neglected, unskilled and lacked the requisite social security in the event of poor governance, low education, poor investment environment and other essential qualities of lives, youths becomeliability, threat and object of national instability to their country. Against this backdrop, this paper attempts an assessment of youths’ protests, its causes and implications in view of the agitations that swept across the nation tagged “EndSARS”. This piece employs discourse analysis and uses secondary sources of data. While many researches had looked into youth protests mostly in the advanced countries, Africa generally, only a few assessed youth protests in Nigeria so far. Hence, this effort is undertaken to deepen the understanding of the EndSARs as a youths uprising in Nigeria. The paper argues that the protest is more of reflection of the societal decadence emanated from poor governance that had encapsulated the country for long than the behaviours of Special Anti –Robbery Squad (SARs) operative that ignited it. In the concluding remarks, the paper urges Nigerian leaders and citizens at the helms of authority to address human rights abuses perpetuated bythe SARs and other security agencies, youth unemployment, poverty and culture of impunity thatheralded and sustained societal ills that made lives miserable for youths given its future dangers if left unaddressed.